2021
DOI: 10.1007/s11325-021-02324-0
|View full text |Cite
|
Sign up to set email alerts
|

Scleroderma and obstructive sleep apnea: a consideration of immunological aspects and the role of fibrosis

Abstract: Sleep disorders are known to be related to autoimmune diseases due to the inflammatory and immunological imbalance induced by or aggravating poor sleep [1]. In this context, we are writing to discuss a relationship that needs to be more clearly understood, that between obstructive sleep apnea (OSA)-a widely prevalent sleep breathing disorder [2]and scleroderma-an autoimmune disease that can affect breathing through a number of mechanisms, including lung fibrosis. We highlight pathological and immunological fea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These patients with significant ILD belong to WSPH Group 3 (PH diseases due to lung diseases and/or hypoxia). The presence of comorbid obstructive sleep apnea among patients with SSc ranges up to 50% and must be evaluated as this can contribute to changes seen in diagnostic modalities (46)(47)(48)(49). There are also increased rates of thromboembolism which can lead to the development of chronic thromboembolic pulmonary hypertension (Group 4).…”
Section: The Importance Of Phenotyping Pulmonary Hypertension In Scle...mentioning
confidence: 99%
“…These patients with significant ILD belong to WSPH Group 3 (PH diseases due to lung diseases and/or hypoxia). The presence of comorbid obstructive sleep apnea among patients with SSc ranges up to 50% and must be evaluated as this can contribute to changes seen in diagnostic modalities (46)(47)(48)(49). There are also increased rates of thromboembolism which can lead to the development of chronic thromboembolic pulmonary hypertension (Group 4).…”
Section: The Importance Of Phenotyping Pulmonary Hypertension In Scle...mentioning
confidence: 99%
“…Additionally, a significant correlation was identified between mean pulmonary artery diameter and OSA severity indices, namely the apnea-hypopnea index (AHI) and the oxygen desaturation index (ODI) [11]. It has been suggested that fibrosis associated with scleroderma may exacerbate OSA symptoms by affecting lung and airway function [12]. The systemic inflammation and fibrotic processes characteristic of SSc may predispose patients to both esophageal dilation and OSA.…”
Section: Introductionmentioning
confidence: 99%